2015
DOI: 10.1111/dmcn.12737
|View full text |Cite
|
Sign up to set email alerts
|

Valproate‐induced enuresis: a prospective study

Abstract: AIM The aim of this study was to determine the frequency and characteristics of secondary enuresis in children initiated on valproate treatment.METHOD This was a prospective study conducted in children aged 5 to 12 years with suspected newly diagnosed epilepsy and maintained on valproate for at least 1 month. Adverse events spontaneously reported by parents were recorded at each follow-up visit. In addition, we specifically asked about enuresis and other side effects known to occur with valproate treatment. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In 2015, Yamak et al performed a perspective study on 72 epileptic children aged 8 years and 7 months (range 5 -12 years) consuming sodium valproate (as monotherapy). The enuresis caused by sodium valproate was present in 24% of their cases in a mean time period of 19.8 days after exposure (13). This study, which is more similar to results from the current study, showed a higher range of enuresis rate that might be due to different factors such as genetic and/or epigenetic variations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In 2015, Yamak et al performed a perspective study on 72 epileptic children aged 8 years and 7 months (range 5 -12 years) consuming sodium valproate (as monotherapy). The enuresis caused by sodium valproate was present in 24% of their cases in a mean time period of 19.8 days after exposure (13). This study, which is more similar to results from the current study, showed a higher range of enuresis rate that might be due to different factors such as genetic and/or epigenetic variations.…”
Section: Discussionsupporting
confidence: 86%
“…According to the literature, these side effects are more likely to occur in patients who require dosage increase. Despite these reports, there is a lack of solid evidences on association of urinary complications with sodium valproate and thus these complications are not known as side effects of this drug (11,13,14). Egger and Brett performed a retrospective study on the side effects of sodium valproate on epileptic children focusing on weight gain, they showed that among 100 cases, only 7% exhibited enuresis as a side effect (15).…”
Section: Discussionmentioning
confidence: 99%
“…25 Previous research studies assessing the side effects of valproic acid found that nocturnal enuresis was a potential reaction to this medication, with a documented frequency of 7% to 24%. 12,26,27 The frequency of nocturnal enuresis in our study was 10.7% (28 patients), which was similar to prior studies. Nocturnal enuresis was reported by the parents in only 12 of the 260 cases (4.6%) in our study; the remaining 16 cases were detected by specifically asking about nocturnal enuresis, because this side effect is usually under-reported by parents.…”
Section: Children With Enuresissupporting
confidence: 91%
“…10 However, more recent studies reported a variable incidence of valproic acid-induced nocturnal enuresis of 2.2% to 24%. 11,12 Three major factors hypothesized to be behind enuresis are increased nocturnal urine production, detrusor hyperactivity, and impaired arousal process. Both the arousal process and the micturition reflex are mediated by nuclei in the brain stem.…”
mentioning
confidence: 99%
“…Valproic acid is considered a safer alternative to phenytoin for the treatment of adult onset epilepsy [5][6][7][8]. Side effects including anorexia, vomiting, and sleep alterations were the most commonly reported in clinical records [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%